Pondicherry Tourism Mobile Application Development - Dr. P. Sivakumar; Ragavendran. R; Rajan. E; Ramesh. K; Sathishbabu. S (The Bioscan, 2026)
The "Pondicherry Tourism Mobile Application Development" aims to help users easily plan and manage their travel to Pondicherry. It will allow users to explore places, find budget-friendly stays and transport options, and access travel services in one app. Currently, there is a gap in the market for a travel app that promotes domestic tourism with accurate information and a user friendly interface, especially for areas like Pondicherry. Many existing apps need strong internet connections and are hard to use. This project focuses on creating an easy-to-use app that works even with limited internet and supports tourism in the region. To better understand what user want, the study collected feedback from locals and frequent travelers. The results showed that while most people are familiar with travel apps, they felt neutral about the problems they faced using them. The proposed app will include features like details of local attractions, hotels, restaurants, events, transportation options, and more. It will also promote local culture, heritage, and natural beauty to make the user experience memorable and enjoyable. The main goal is to build a convenient, informative, and accessible mobile application that helps both tourists and local residents. By filling the gaps in current travel solutions, the PY-Trips app will make travel in Pondicherry easier, support local businesses, and boost tourism. Its simple design, offline access, and social features will help users connect with the unique charm of Pondicherry, improving both travel experience and cultural appreciation.